Ecological Shifts of Supragingival Microbiota in Association with Pregnancy - Lin, Wenzhen; Jiang, Wenxin; Hu, Xuchen; Gao, Li; Ai, Dongmei; Pan, Hongfei; Niu, Chenguang; Yuan, Keyong; Zhou, Xuedong; Xu, Changen; Huang, Zhengwei (Frontiers in Cellular and Infection Microbiology, 2018)
Pregnancy is a physiological process with pronounced hormonal fluctuations in females, and relatively little is known regarding how pregnancy influences the ecological shifts of supragingival microbiota. In this study, supragingival plaques and salivary hormones were collected from 11 pregnant women during pregnancy (P1, ≤14 weeks; P2, 20–25 weeks; P3, 33–37 weeks) and the postpartum period (P4, 6 weeks after childbirth). Seven non-pregnant volunteers were sampled at the same time intervals. The microbial genetic repertoire was obtained by 16S rDNA sequencing. Our results indicated that the Shannon diversity in P3 was significantly higher than in the non-pregnant group. The principal coordinates analysis showed distinct clustering according to gestational status, and the partial least squares discriminant analysis identified 33 genera that may contribute to this difference. There were differentially distributed genera, among which Neisseria, Porphyromonas, and Treponema were over-represented in the pregnant group, while Streptococcus and Veillonella were more abundant in the non-pregnant group. In addition, 53 operational taxonomic units were observed to have positive correlations with sex hormones in a redundancy analysis, with Prevotella spp. and Treponema spp. being most abundant. The ecological events suggest that pregnancy has a role in shaping an at-risk-for-harm microbiota and provide a basis for etiological studies of pregnancy-associated oral dysbiosis.